Kinetics and capacity of phosphorus extraction from solid residues obtained from wet air oxidation of sewage sludge. (15th April 2019) - Barca, Cristian; Martino, Mathieu; Hennebert, Pierre; Roche, Nicolas
Highlights: Sewage sludge residues from wet air oxidation show a high potential for P recovery. 1 M citric acid and 1 M HCl were the most efficient solutions for P extraction. P extraction capacity stabilized around 80 g P/kg residue after 2 h of contact time. P extraction occurred predominantly via dissolution of Ca bound P compounds. Abstract: Solid residues from thermal treatments of sewage sludge (SS) represent a valuable source of phosphorus (P) for the fertilizer production. This study aims at evaluating the P recovery potential from solid residues obtained from wet air oxidation of SS under subcritical water conditions (WAO residues). A series of P extraction experiments was performed by acidic and alkaline leaching at different liquid to solid ratios. Hot chemical extractions and P fractionations were also carried out to characterize the chemical composition of the WAO residues. The main objectives of this work were to determine the best operating conditions for P extraction, and to describe and understand the kinetics and the main mechanisms leading to P release. The results obtained in this study indicate that 1 M citric acid and 1 M HCl at the liquid to solid ratio of 10 L/kg can extract 61% and 65% of the total P content after 2 h of contact time at room temperature, thus giving P extraction capacities of 81 and 86 g P/kg WAO residues, respectively. The analysis of kinetic data indicates that P extraction with 1 M HCl is faster, but 1 M citric acid can give higher P extraction efficiencies at the equilibrium. The molar ratios of Ca to P of the leachates suggest that P extraction from WAO residues was primarily due to the dissolution of a mixture of various Ca-P complexes.